Comparison of Water Quality Monitoring Between Citizen Science and Researchers: A Case Study in The Bantimurung River - Zefanya, Anastasia; Rahmatika, Iftita (Al-Makki Publisher, 2025)
The Bantimurung River, a vital water source in the UNESCO-listed Maros Karst Area, faces increasing pollution threats from anthropogenic activities. While conventional water quality monitoring by experts is accurate, its high cost and limited scalability hinder widespread implementation, particularly in developing regions. Citizen science has emerged as a promising alternative, offering cost-effective and participatory environmental monitoring. However, questions remain about the reliability of data collected by non-experts. This study compares water quality measurements—including temperature, pH, dissolved oxygen (DO), nitrite, ammonia, and phosphate—taken by citizen scientists and professional researchers in the Bantimurung River. Data were collected at seven sampling points over four weeks, using both field test kits and laboratory analyses. Statistical methods, including Shapiro-Wilk normality tests, paired t-tests, Wilcoxon Signed-Rank tests, and linear regression, were employed to evaluate data consistency. Results revealed high accuracy for physical parameters (pH, temperature, DO), with insignificant mean differences and strong correlations (R² > 0.7). However, chemical parameters (nitrite, ammonia, phosphate) showed significant discrepancies due to limitations in portable tools and field procedures. The findings highlight the potential of citizen science for scalable monitoring of basic water quality indicators, while underscoring the need for tool calibration and laboratory validation for precise chemical analysis. This research contributes to the growing discourse on participatory environmental monitoring, offering practical insights for policymakers and conservationists. By integrating citizen science with professional methods, sustainable water quality monitoring can be achieved, balancing cost-efficiency and accuracy in ecologically sensitive areas.